Hubungan Beban Kerja Dengan Kepuasan Kerja Perawat Di Rumah Sakit Bhayangkara Tingkat III Palangka Raya - Dwi Agustian Faruk; Ayu Puspita; Romy Irawan Patiku (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Nursing services are an integral part of healthcare in hospitals. Nursing staff are responsible for providing optimal nursing services to improve and maintain the quality of nursing care. This will affect day-to-day performance if not balanced with increased knowledge, skills, and supporting factors to enhance job satisfaction, as it will be perceived as a heavy workload. This study aims to determine the relationship between workload and job satisfaction of nurses at Bhayangkara Level III Hospital in Palangka Raya. The research design used is correlational with a cross-sectional method. The instruments used in this study were questionnaires and the Spearman Rank statistical test directed to 30 Police Nurses at Bhayangkara Level III Hospital in Palangka Raya. The results of the workload research show that 17 respondents (85.0%) are "satisfied" with their work in the heavy category. The significance value of the relationship between workload and job satisfaction of nurses at Bhayangkara Level III Hospital is 0.280 > 0.05, where H1 is rejected. The correlation coefficient value in this study is weak, which is 0.204. Thus, H1 is rejected, meaning there is no relationship between workload and job satisfaction of nurses at Bhayangkara Level III Hospital in Palangka Raya. The conclusion is that the heaviness or lightness of the workload does not affect job satisfaction if the job satisfaction indicators are fulfilled, such as job suitability, colleagues, salary, promotion opportunities, supervision, and facilities.